The moral ecology of markets : assessing claims about markets and justice - Finn, Daniel K., 1947- (Cambridge University Press, 2006)
"Disagreements about the morality of markets - and about self-interested behavior within markets - run deep. They arise from widely differing perspectives within economics and political philosophy that appear to have nothing in common. In this book, Daniel Finn provides a framework for understanding these conflicting points of view. Recounting the arguments for and against markets and self-interest, he argues that every economy must address four fundamental problems: allocation, distribution, scale, and the quality of relations. In addition, every perspective on the morality of markets addresses explicitly or implicitly the economic, political, and cultural contexts of markets, or what Finn terms "the moral ecology of markets." His book enables a dialogue among the various participants in the debate over justice in markets.